Targeting the gut–lung microbiota axis by means of a high-fibre diet and probiotics may have anti-inflammatory effects in COVID-19 infection. (June 2020) - Conte, Luana; Toraldo, Domenico Maurizio
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) 1 is a 2019 novel coronavirus, which only in the European area has led to more than 300, 000 cases with at least 21, 000 deaths. This manuscript aims to speculate that the manipulation of the microbial patterns through the use of probiotics and dietary fibers consumption may contribute to reduce inflammation and strengthen the immune system response in COVID-19 infection. The reviews of this paper are available via the supplemental material section.